2023
DOI: 10.1101/2023.02.15.528622
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Specialized actin nanoscale layers control focal adhesion turnover

Abstract: Focal adhesions (FAs) connect inner workings of the cell to the extracellular matrix to control cell adhesion, migration, and mechanosensing. Previous studies demonstrated that FAs contain three vertical layers, which connect extracellular matrix to the cytoskeleton. However, cellular processes rely on precisely-regulated FA turnover, but the molecular machineries that control FA assembly and disassembly have remained elusive. By using super-resolution iPALM microscopy, we identified two unprecedented nanoscal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…Structural analysis using cryoEM has now revealed that Tpm isoforms may exert differential functions via different modes of binding and controlling accessibility of ABPs like myosin and cofilin to F-actin 29,30 . How Tpm isoforms have been fine-tuned to perform distinct spatial sorting and functions during evolution remains an active area of research and their crosstalk during recruitment and maturation within the same actin structure is just beginning to be understood 21,31 .…”
Section: Introductionmentioning
confidence: 99%
“…Structural analysis using cryoEM has now revealed that Tpm isoforms may exert differential functions via different modes of binding and controlling accessibility of ABPs like myosin and cofilin to F-actin 29,30 . How Tpm isoforms have been fine-tuned to perform distinct spatial sorting and functions during evolution remains an active area of research and their crosstalk during recruitment and maturation within the same actin structure is just beginning to be understood 21,31 .…”
Section: Introductionmentioning
confidence: 99%